PENGARUH PRENATAL MASSAGE TERHADAP NYERI PUNGGUNG BAWAH IBU HAMIL TRIMESTER III - Andriyani, Asti; Paryono, Paryono (Medical Journal of Nusantara, 2023)
Background: Painful back lower mother pregnant is disturbance on bone and muscle part lower back caused _ by activity body that doesn't ergonomic. Prenatal massage on mother pregnant aim as effort for reduce common complaints. Research Objectives: For knowing Influence Prenatal Massage to Decrease Painful Back Lower on Mother Third Trimester Pregnant. Method Research: Study this is study quantitative with design quasi experiment use approach one group pre post test design. Sampling technique in study this is non- probability sampling with method purposive sampling. Sample used _ in study this as many as 50 mothers third trimester pregnant with complaint painful back below that has been Fulfill criteria inclusion in District Dlingo Bantul Yogyakarta. Results show almost whole respondent (96%) mother pregnant trimester III experience painful back lower with scale painful medium. Results Test Wilcoxson showing on p value = .000. Conclusion: There is influence prenatal massage against drop painful back on mother third trimester pregnant in subdistrict Dlingo Bantul Yogyakarta.